Current Situation of the Business Continuity Plan Preparation in Japan: Community General Support Centers - Iguchi, Aya; Ishida, Chie; Sato, Taichi; Okada, Risa; Kanesaka, Takayuki; Kanno, Taro (Journal of disaster research, 2023)
Objective: This study aims to clarify the actual situation of the business continuity plan (BCP) preparation in the community general support centers in Japan. Method: In September 2021, a survey was administered to 5,391 community general support centers all over Japan using a self-input Web questionnaire. Results: 577 responses were obtained, for a response rate of 10.7%, among which “BCP has been created” accounts for 9.5%; “BCP has not been created, and there is no plan to create any,” 22.0%; “it is currently being examined whether to create BCP,” 47.0%; and “BCP is now being created,” 21.5%. The community general support centers that “have not determined the division of roles” with their municipalities in responding to disaster account for 64%. Conclusions: This study clarifies the situation of the community general support centers in Japan, based on which they cannot be said to be prepared for a disaster. From the word network of answers to our questionnaire, we can see reasons why the BCP has not been created: lack of knowledge and busy work. Centers that have not prepared a BCP, understand the need to create one, but they are too busy and are unaware of how to do so. We discuss measures to promote the creation of BCPs by community general support centers in the future, given the current situation.